Uso da concha de marisco na formulação de fluidos de perfuração de petróleo - Viana, Luara Ribeiro (2021)
Additives impart special properties to drilling fluids. Choosing the right choice with the right properties has a profound impact on drilling success and overall well costs. Shellfish shells are waste products from shellfish consumption. These shells are rich in calcium carbonate (CaCO3), an additive widely used in fluids as a filling agent. The objective of this work is to use shellfish shell powder (PCM) as an additive in microemulsified drilling fluids. A preliminary study was developed to obtain the best particle size range for the use of PCM and the best concentration of xanthan gum. The determination of two microemulsified systems was carried out in order to observe the behavior of PCM in different systems, the first system consists of a ternary mixture composed of pine oil, alkonat L 100 W surfactant and glycerin/water and the second system is formed by pequi oil, alkosynt 9160 surfactant and glycerin/water. Right after the preparation of the microemulsions (ME), two points were chosen in each diagram, an oil-in-water (O/A) and a water-in-oil (A/O) point. Then, eight fluids were prepared using microemulsions as a base and shell powder as a filling agent. Calcium carbonate fluids were prepared for comparison purposes. The properties of the fluids were evaluated through rheological, aging, filtrate volume, high pressure and high temperature (HPHT) rheology, thermal degradation, permeability, pH and density tests. The best concentration of xanthan gum was 0.5% and the particle size range of PCM used was 74 μm. O/A fluids performed better compared to A/O. For the fluid prepared with ME1 O/W, added with powder from shellfish shells, the specific mass was 1.09 g/cm3 and an apparent viscosity of 67.75 cP, not far from the data presented by the fluid added with calcium carbonate. The fluid prepared with ME2 O/W and added with powder from shellfish shells had a specific mass of 1.13 g/cm3 and an apparent viscosity of 68.5 cP, compared to the fluid formulated with calcium carbonate, not has large discrepancies. The fluids formulated with PCM and CaCO3 showed very similar behavior, making the use of PCM a viable alternative to act as a filling agent for microemulsified base drilling fluids. Generating use of solid waste, adding value to this waste and creating new sources of income for residents of communities that work with seafood.